Is prior parental criminal justice involvement associated with child maltreatment? A systematic review. (September 2016) - Austin, Anna
Abstract: Parental criminal justice involvement is prevalent in the United States and potentially associated with a range of negative outcomes for children including child abuse and neglect. However, the association between prior parental criminal justice involvement and child maltreatment is not well understood. This paper reviewed the existing literature regarding maltreatment victimization among children of parents with prior criminal justice involvement. Results from ten reviewed studies demonstrated an association between prior parental criminal justice involvement and child maltreatment, but did not provide sufficient evidence to determine whether parental criminal justice involvement is an independent risk factor for child maltreatment or of the specific mechanisms through which this association occurs. Recommendations for future research include use of multivariate analysis methods that account for variations in the type and timing of parental criminal justice involvement and child maltreatment. Implications for practice include the development of strategies to address the adverse family contexts commonly found among these parents and children. Highlights: Ten studies have examined the association between prior parental criminal justice involvement and child maltreatment. Across studies, an association between prior parental criminal justice involvement and child maltreatment was demonstrated. However, it is unclear whether parental criminal justice involvement is an independent risk factor for child maltreatment.